Lunar meteoritic gardening rate derived from in situ LADEE/LDEX measurements - Jamey R. Szalay; Mihály Horányi (Geophysical Research Letters)
Abstract The Lunar Atmosphere and Dust Environment Explorer (LADEE) orbited the Moon for approximately 6 months, taking data with the Lunar Dust Experiment (LDEX). LDEX was uniquely equipped to characterize the current rate of lunar impact gardening as it measured the very particles taking part in this process. By deriving an average lunar dust density distribution, we calculate the rate at which exospheric dust rains back down onto the lunar surface. Near the equatorial plane, we find that approximately 40 μm/Myr of lunar regolith, with a cumulative size distribution index of 2.7, is redistributed due to meteoritic bombardment, a process which occurs predominantly on the lunar apex hemisphere.